Innovative sustainable conversion from CO2 and biodiesel-based crude glycerol waste to bio-based polycarbonates. (December 2019) - Cui, Shaoqing; Borgemenke, Joshua; Liu, Zhe; Keener, Harold M.; Li, Yebo
Graphical abstract: An innovative sustainable conversion process to produce bio-based polycarbonates from industrial crude glycerol waste and CO2 was developed, providing a new platform for biodegradable plastics production. Highlights: New conversion from CO2 and fatty acid waste to bio-based polycarbonate was developed. Epoxy monomer was obtained from crude glycerol-fatty acid waste via one-pot process. Bio-based polycarbonate film exhibited competitive properties. Bio-based polycarbonates were first-time produced from CO2 and crude glycerol waste. New sustainable platform to utilize industrial wastes was provided. Abstract: An innovative and sustainable conversion to produce bio-based polycarbonates from carbon dioxide (CO2 ) and crude glycerol-fatty acids waste were developed. Crude glycerol, the byproduct of industrial biodiesel process, mainly composed of fatty acids, glycerol, and impurities. Bio-based Epoxide monomers were successfully produced from fatty acids residues waste from crude glycerol refining process with bio-based ephichlorohydrin derived from refined crude glycerol donating epoxy group. Bio-based polycarbonates were successfully synthesized through copolymerizing CO2 and obtained bio-based epoxide monomers, giving carbonate linkages of 98.1%. The effects of impurities from raw crude glycerol on the properties of obtained bio-based polycarbonates were found to be trivial. The bio-based polycarbonates plastic film exhibited good transparency, stable thermal property (thermal decomposition at ˜230 °C), and good mechanical properties (tensile strength of 1.69 MPa, elongation of 59.6%). This developed innovative conversion may provide a new platform to convert CO2 and industrial residues wastes to biodegradable bio-based plastics, affording solutions for environmental challenges.